1998
DOI: 10.1046/j.1365-3083.1998.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‐Induced Synthesis of Interleukin‐5, but not of IgE, is a Key Mechanism Linked to Symptomatic Episodes of Seasonal Allergic Rhinitis in Sensitized Individuals

Abstract: Some individuals with detectable levels of Japanese cedar (Criptomeria japonica) pollen-specific immunoglobulin (Ig)E in serum have no apparent nasal symptoms during the pollen season. The response of CD4+ T-helper (Th) cells to the pollen allergen might differ fundamentally between asymptomatic and symptomatic individuals who are already sensitized to the pollen. The aim of this study was to discern the possible differences in responses of peripheral blood mononuclear cells (PBMCs) to the pollen allergen betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
2
25
1
Order By: Relevance
“…According to current thinking, atopic allergy might be defined as a TH2 cell or allergen-induced TH2 response predominant inflammatory disease. A key factor involved in allergic diseases is undoubtedly allergen-specific IgE to a particular environmental allergens (24), and PBMCs from allergic patients produce larger amounts of IgE than those from non-atopic individuals (16,25). In the present study, the level of IgE produced by PBMCs in the presence of shoseiryu-to were significantly lower than those in the absence of the agent, although the significance was weak (p =0.0415).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…According to current thinking, atopic allergy might be defined as a TH2 cell or allergen-induced TH2 response predominant inflammatory disease. A key factor involved in allergic diseases is undoubtedly allergen-specific IgE to a particular environmental allergens (24), and PBMCs from allergic patients produce larger amounts of IgE than those from non-atopic individuals (16,25). In the present study, the level of IgE produced by PBMCs in the presence of shoseiryu-to were significantly lower than those in the absence of the agent, although the significance was weak (p =0.0415).…”
Section: Discussioncontrasting
confidence: 45%
“…Expression of mRNA for IL-5 has been detected in bronchial biopsies of asthmatic patients, and the expression of IL-5 mRNA has tended to increase in severe disease (27). IL-5 is a key cytokine linked to symptomatic episodes of allergic rhinitis and asthma in sensitized individuals (25,28). In addition, treatment with anti-IL-5mAb could inhibit the development of hyper-responsiveness (29).…”
Section: Discussionmentioning
confidence: 99%
“…These authors have found that neutrophils were regulated through activation of IL-8. Ex vivo stimulation of peripheral blood mononuclear cells of patients with symptoms of seasonal allergic rhinitis with Japanese cedar pollen allergen Cry j induced synthesis of IL-5 (Ohashi et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The details and justification of the methods employed in this study have been described elsewhere (19,(22)(23)(24).…”
Section: Determination Of Il-4 Il-5 and Ifn-k In Culture Supernatantsmentioning
confidence: 99%
“…The seasonal rise in TH2-type cytokines in seasonal allergic rhinitis is likely to be due to the increased reactivity of TH cells in response to the natural allergen exposure during the pollen season. Indeed, allergen-induced synthesis of TH2-type cytokines by TH cells is significantly greater in patients with seasonal allergic rhinitis than in non-atopic individuals (19). However, it remains unclear whether this increased reactivity of TH cells of patients with seasonal allergic rhinitis is an allergen-specific or a general immune enhancement.…”
Section: Introductionmentioning
confidence: 99%